Regulador eletromagnético de frequência aplicado no controle de velocidade de geradores eólicos - Silva, Paulo Vitor (2015)
The constant necessity for new sources of renewable energy is increasingly promoting the increase of investments in this area. Among other sources, the wind power has been becoming prominent. It is important to promote the search for the improvement of the technologies involved in the topologies of the wind turbines, seeking for alternatives which enhance the gotten performance, despite the irregularity of the wind speed. This study presents a new system for speed control, in this case applied to the wind turbines - the Electromagnetic Frequency Regulator (EFR). One of the most used devices in some topologies is the mechanical gearboxes which, along with a short service life, often represent sources of noise and defects. The EFR does not need these transmission boxes, representing a technological advancement, using for that an adapted induction machine, in which the stator becomes mobile, supportive to the axis of the turbine. In the topology used in this study, the EFR also allows us to leave out the usage of the eletronic converters to establish the coupling between the generator and the electrical grid. It also the reason why it provides the possibility of obtaining the generation in alternating current, with constant voltage and frequency, where there is no electrical grid. Responsable for the mechanical speed control of the generator, the EFR can be useful in other transmission systems in which the mechanical speed control output is the objective. In addition, the EFR operates through the combination of two inputs, a mechanical and other electrical. It multiplies the possibilities of application because it is able to synergistic coupling between different arrays of energy, and, for such reasons, it enables the various sources of energy involved to be uncoupled from the network, being the synchronous generator responsible for the system connection with the electrical grid, simplifying the control strategies on the power injected in it. Experimental and simulation results are presented through this study, about a wind turbine, validating the proposal related to the efficience in the speed control of the system for different wind conditions.